Arthroscopic Superior Capsular Reconstruction for Treatment of Massive Irreparable Rotator Cuff Tears - Hirahara, Alan M. (Arthrosc Tech, 2015)
Massive irreparable rotator cuff tears have been troublesome entities to treat, especially in younger patients. Few good options exist, leaving most patients in recent years receiving a reverse total shoulder arthroplasty. Reverse shoulder arthroplasty carries serious risks, a limited lifespan, and no other viable options should it fail. Recent biomechanical studies have shown that the superior capsule is critical to containing the glenohumeral joint reduced, allowing the larger muscles like the deltoid and pectoralis major to function properly. The superior capsular reconstruction is an anatomic reconstruction of the superior capsule to restore the normal restraint to superior translation that occurs with a deficient rotator cuff. The technique described in this article is an arthroscopic reconstruction of the superior capsule with dermal allograft.